Coumarins, psoralens, and quantitative 1H-NMR spectroscopy for authentication of lemon (Citrus limon [L.] Burm.f.) and Persian lime (Citrus × latifolia [Yu.Tanaka] Tanaka) juices. (15th October 2021) - Jungen, Markus; Lotz, Philipp; Patz, Claus-Dieter; Steingass, Christof B.; Schweiggert, Ralf
Highlights: Coumarins/psoralens (C/P) by HPLC are helpful markers in Citrus juice authentication. Proven lime markers were confirmed and extended by 5-geranyloxy-8-methoxypsoralen. Varying C/P shares were observed in flavedo, albedo and endocarp of limes and lemons. NMR alone or combined with C/P data seemed also helpful for authentication. Levels of C/P correlated with processing intensity, but not juice yield. Abstract: Mutual adulterations of lemon and lime juices may be detected using coumarins and psoralens as markers. Poor manufacturing practices or legal but mechanically intense processing of lemons were recently suspected to lead to false accusations of deliberate adulterations with lime juices due to potentially unspecific markers. Therefore, we studied coumarin and psoralen profiles in carefully dissected flavedo, albedo, and endocarp of lime and lemon as well as in juices produced under variable mechanical stresses at laboratory and pilot plant scale. Although the marker herniarin was detectable in juices from lime and harshly extracted lemons at low levels, isopimpinellin, bergapten and the herein proposed, tentatively assigned 5-geranyloxy-8-methoxypsoralen represented unambiguously lime-specific markers. Coumarin and psoralen data also allowed differentiating juices produced at differing degrees of mechanical stress. The latter was also possible using quantitative 1 H-NMR spectroscopy, which yielded best results when combined with HPLC data on coumarins and psoralens. In the future, the reported approach may be used for establishing a robust database prior to being used in industrial practice.